Penerapan Teori Hukum Alam Dalam Legalitas Kepemilikan Tanah - Alisya Rahma Saebani; Yohana Sekar Pawening; Taufiqurrohman Syahuri (Jurnal Hukum dan Sosial Politik, 2024)
Natural law is everything that exists in accordance with the rules of the universe. This law also proves that there are fundamental demands in human life that are evident in their existence as reasonable beings. Humans should not follow their irrational instincts, but rather considerations of reason and moral sense. In Indonesia, this is regulated in Law No. 5/1960 on the Basic Regulation of Agrarian Principles (UUPA). With the regulation of this Law, the Indonesian people have the legality of land ownership in this case the rights and legal protection for the land owned and used for survival. But currently there is still a lack of socialization of rural communities, especially inland, of the importance of ownership of legal land ownership certificates.